SPACE STRUCTURE OF ANTIQUE ESHERA SETTLEMENT FROM HIGH-PRESICION MAGNETIC PROSPECTING - Bondar, K.; Erlikh, V.; Virshylo, I.; Kravchenko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper discusses the results of high-precision magnetic measurements on Eshera settlement - the unique fortification structure of ancient times. Peculiarities of the settlement plan and separate buildings were discovered, from archaeological interpretation of geophysical anomalies.